Pulmonary thromboembolic disease in COVID-19 patients on CT pulmonary angiography – Prevalence, pattern of disease and relationship to D-dimer - Ooi, M.W.X. (Eur J Radiol, 2020)
OBJECTIVES: To define the prevalence of pulmonary thromboembolic (PTE) disease diagnosed on CT pulmonary angiography (CTPA) in COVID-19 patients. To assess distribution of PTE and to evaluate for association between severity of COVID-19 disease, D-dimer values and incidence of PTE. METHODS: Patients with diagnosis of COVID-19 presenting to 5 different hospitals across Greater Manchester between 1st March 2020 and 30th April 2020 who had CTPA were included. CTPA images were evaluated for presence of PTE, distribution of PTE (in small and/or large vessels) and distribution of PTE within lungs with or without COVID-19 CT changes. Severity of COVID lung changes were graded. D-dimer values within 72 h of CTPA were obtained. Statistical analyses were performed to evaluate for any significant association between variables. p values of ≤0.05 were regarded as statistically significant. RESULTS: A total of 974 patients presented across five hospital sites with COVID-19 infection. Eighty-four (n = 84) COVID-19 patients underwent CTPA. Of these, 38 % (32/84) had PTE. PTE was seen in small vessels in 75 % (24/32) and in lungs demonstrating COVID-19 changes in 72 % (23/32). 84 % (27/32) of PTE positive patients had disease severity of moderate or higher score (p = 0.005). D-dimer values were significantly higher (p ≤ 0.001) in PTE patients, median value in PTE group was 6441mcg/L (range 219-90925). A D-dimer cut off value of 2247mcg/L provides sensitivity of 0.72 and specificity of 0.74. CONCLUSION: There is increased prevalence of PTE in patients with moderate to severe COVID-19 disease. D-dimer values may have potential in guiding anticoagulation therapy and prognostication.